PENGEMBANGAN MEDIA PEMBELAJARAN PETA INTERAKTIF BERBASIS AUGMENTED REALITY PADA MATERI KEANEKARAGAMAN FLORA DAN FAUNA DI INDONESIA KELAS V SDN 104204 SAMBIREJO TIMUR T.A 2025/2026 - Citra Kharisma Silitonga; Yusra Nasution; Wildansyah Lubis; Irsan; Tiarnita Maria Sarjani Br. Siregar (STKIP Subang, 2026)
This study employed the ADDIE development model to develop an Augmented Reality-based Interactive Map learning media on the topic of biodiversity of flora and fauna in Indonesia for Grade V students at SD Negeri 104204 Sambirejo Timur in the second semester of the 2025/2026 academic year. The research subjects consisted of 20 fifth-grade students, 2 expert validators to assess the validity of the media, and 1 classroom teacher to evaluate its practicality in IPAS learning within the Merdeka Curriculum. The validation results from material and media experts indicated that the Augmented Reality-based Interactive Map learning media was categorized as highly feasible, with high percentages based on content, design, and language aspects. The practicality test conducted by the teacher and students also showed that the media was highly practical for use in learning, as reflected in students’ positive responses with assessment percentages above 90%. The evaluation results revealed a significant improvement in students’ learning outcomes, as evidenced by the comparison between pre-test and post-test scores. The average pre-test scores were in the low category, while the post-test scores increased to the very good category after the implementation of the learning media. Therefore, it can be concluded that the Augmented Reality-based Interactive Map learning media is highly feasible and practical to be used in IPAS learning and is effective in improving students’ understanding of biodiversity of flora and fauna in Indonesia.